PELAKSANAAN EVALUASI LAYANAN INFORMASI YANG DILAKUKAN GURU BK DI SMP NEGERI 11 PADANG (STUDI TERHADAP KELAS VIII) - Sari, Rismailia; Kasih, Fitria; Gusneli, Gusneli (Bimbingan dan Konseling, 2013)
Bassicly, Evaluationgives consideration or value based on certain criteria. There are some problems in the implementation of evaluation particularly on the evaluation of information services. BK teachers have not been able to see the success of the service information provided to students, based on the problem, the researcher was conducted a study on the implementation of the Information Service Evaluation Forum counselor in SMP N 11 Padang. The purpose of theresearchis to describe the implementation of the initial evaluationinformation services, the implementation of evaluation process information services, the implementation of the evaluation result information services. The researcher used descriptive research, population in this study were 189 people, the researcher used purposive sampling,the sample of this research were 60 people. A questionnaire as tool that used in collect the data, technique of data analysis is percentages.Results of this study found that: Implementation Evaluation Services Information Forum counselor in SMP N 11 Padang generally is good in the category, the variable are:1.Implementationinitial evaluation of information services that BK teachers did in SMP N 11 Padang is in the category quite well, 2. Implementation of the evaluation process conducted information services BK teacher in SMP N 11 Padang is also pretty good on the category,3. Implementation of the evaluation result information services evaluation that BK teachersin SMP N11 Padang is in the category quite well.